Retroconversion exercise in an online thesaurus environment: a post cardcatalogue conversion experience at the International Institute of Tropical Agriculture in Ibadan - Adeniran, O.R.; Adigun, A.T. (Emerald Publishing Limited, 1996)
Faced with the need to undertake the retrospective conversion of the library catalogue, we searched the literature for advice and experiences which might prove useful for our situation. However, apart from Crowe and Matthews reporting on OCLC and Dartmouth respectively, there seemed to be little of value to us.